Componentes de varianza y heredabilidad: una revisión de interpretaciones en diferentes casos de estudio (2015)
Heritability provides what ratio of phenotypic characteristics of individuals in a population are result whereas of genetic effects or in any case an effect of genotype – environment interactions. There are two terms - H2 and h2 -, where so even their components are statistical values without some evolutionary sense except if a conception of specie‟s biology is there. It is necessary proof notions on statistics in order to calculate and interpret both H2 and h2. In consequence, although have written special books, it is difficult for students, professors and researches the applications of quantitative genetics in genetic improvement and evolutionary research. In that reason, this review considers different interpretations of heritability with the aim to provide necessary basic concepts from its applied and estimated value to its interpretation, at all in order to become useful the applications. The analyses were carried out focusing exclusively the investigations which estimated hereditability by using only ANOVA into one-way or more than one way. A search of free articles on the web was carried out; studies were reviewed on evolutionary importance related to the life history traits of Drosophila melanogaster and studies related to genetic improvement applied in populations of plant species with economical importance as Thinopyrum ponticum y Lycopersicon sp. The fundamental interpretations of Molina, (1992) on phenotypical model by which the heritability and its components are supported were discussed. Furthermore from Mousseau et al., (1987) observations on the Fundamental theorem of natural selection by Fisher (1930, 1958) were realized. After all realized analyses it was reasonable to argue that the Fundamental theorem of natural selection by Fisher, is a support of most interpretations of heritability, which is a parameter that varies so even with its components in different conditions of analysis. Also the genetics principles that support the Evolutionary 6 synthesis determine the heritability‟s applications to the focuses as Quantitative genetics that is applied to genetic improvement and broad topics as evolutionary biology. Thus is there when heritability takes an important validity once the phenotypical variations are observed by causes of genetic and environmental factors on determined specie by one are known aspects related to its biology.